2021
DOI: 10.1371/journal.pone.0256301
|View full text |Cite
|
Sign up to set email alerts
|

Research on the speed thresholds of trucks in a sharp turn based on dynamic rollover risk levels

Abstract: Truck rollover is a problem that seriously endangers the safety of human life. Under special conditions, when the driver takes a sharp turn, the truck is most prone to rollover. Speed seriously affects the driving stability of the truck in a sharp turn, but the calculation of the safe speed is not accurate enough at present. The aim of this paper is to develop a more accurate safe speed calculation method to avoid the truck rollover in a sharp turn. Firstly, the calculation formula of the rollover threshold wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…This indicates that the direction of lane change is different and the effect of superelevation variables on the safety margins of the SUV is completely opposite. In a study about the critical safety speed of trucks, Xin et al [ 25 ] found that the speed limit threshold is different when the direction of the lane change of the truck is different on the curve. In their study, when the lane change direction was consistent with the curve bending direction, the speed limit threshold was higher, that is, the allowable speed was higher when the rollover safety margin was zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the direction of lane change is different and the effect of superelevation variables on the safety margins of the SUV is completely opposite. In a study about the critical safety speed of trucks, Xin et al [ 25 ] found that the speed limit threshold is different when the direction of the lane change of the truck is different on the curve. In their study, when the lane change direction was consistent with the curve bending direction, the speed limit threshold was higher, that is, the allowable speed was higher when the rollover safety margin was zero.…”
Section: Resultsmentioning
confidence: 99%
“…Yan developed a model for the maximum allowable speed in rain for horizontal curves during emergency braking based on the friction ellipse theory proposed by Radt [ 23 , 24 ]. Xin predicted the safe speed threshold to avoid rollover by simulating the dynamic rollover process of loaded trucks under sharp steering conditions [ 25 ]. Although these results can help reduce the accident risk of collision-averse driving behaviors and provide a theoretical basis for speed limit management schemes, they still cannot quantify road safety margins with collision-averse driving behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the curve alignment of mountain roads may greatly increase the driving difficulty of overcrowded buses, resulting in leaving the carriageway and a large number of casualties. Relatively poor dynamic conditions and a lack of safety measures are the key causes of single crashes in large vehicles [ 43 , 44 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…These accidents often have extremely serious consequences for passengers and cargo [ 1 , 2 ]. The phenomenon of vehicle rollover occurs when the driver suddenly steers at high speed [ 3 ]. At this time, a centrifugal force of great magnitude will appear.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of vehicle rollover occurs when the driver suddenly steers at high speed [3]. At this time, a centrifugal force of great magnitude will appear.…”
Section: Introductionmentioning
confidence: 99%